Perceptions of Chinese traditional food and European food among Chinese consumers. Issue 12 (5th December 2016) - Wang, Ou; Gellynck, Xavier; Verbeke, Wim
Abstract : Purpose: The purpose of this paper is to explore Chinese consumers' perceptions in relation to both Chinese traditional and European food. Design/methodology/approach: A web-based free word association test was administered to 302 consumers in China. They were asked to give the first three words that came into their minds when they were presented with each of two stimulus words, "traditional food" and "European food". Three researchers grouped the elicited words into classes and then into dimensions. χ 2 association tests were used to assess and identify statistically significant differences in the frequencies of classes and dimensions for the two food concepts between socio-demographic groups. Findings: The findings show that Chinese consumers define Chinese traditional food and European food through ten similar dimensions: Sensory appeal, Health, Origin, Marketing, Safety, Variety, Heritage, Symbolic meaning, Simplicity and Mood. Additionally, they associate Chinese traditional food with the dimensions Elaboration, Celebration and Habit, as well as link European food to the dimensions Convenience and New. Although ten dimensions are the same, obvious differences can be identified by comparing the classes for the two food concepts. Further, there are significant differences in the class associations for European food between age groups and in the dimension associations for Chinese traditional food between gender groups. Originality/value: By using an online qualitative research method, this study is one of the first to address how Chinese consumers define both European food and their own traditional food in China, the largest East Asian country. The findings are particularly useful for the future development of traditional food products and for the future export of European food products onto China and even other countries in East Asia.